ANALISIS DAMPAK PEMEKARAN WILAYAH TERHADAP PENDAPATAN PERKAPITA DIKABUPATEN KERINCI - Murniati Murniati (J-MAS (Jurnal Manajemen dan Sains), 2017)
The Indonesian nation has reformed the governance since the enactment of Law No.22 of 1999 on Regional Government. Since then innovative ideas and experiments have been conducted to improve the implementation of regional autonomy and decentralization in order to improve public services and poverty alleviation effectively. One of the most important aspects of the current implementation of regional autonomy is related to the division and merger of regions which aims to strengthen the relationship between local government and local communities in order to grow democratic life. Kerinci regency is one of the districts located at the western end of Jambi Province. This regency is one of the oldest districts in Jambi Province which has been established as a district in Jambi Province since the province was officially established. Kota Sungai Penuh is an expansion of Kerinci Regency established through Law Number 25 Year 2008 regarding the Formation of Full River City in Jambi Province. Based on the results and discussion it can be concluded that this study proves that there is a difference of Per Capita income in Kerinci Regency 2005-2013, four years before pemekaran (2005-2008) with four years after pemekaran (2010-2013), this is proved by Count> t table or 9.991> 3.18245. There needs to be a more targeted program and policy making for the development of Kerinci Regency and the economic development of the community as well as resolving the economic problems that exist in Kerinci regency so that pemekaran is not merely limited to the formulation of articles related to eligibility, and the process of expansion but also policy Which is able to meet the needs of the community and the development of the Regency in order to move forward. The need for support from all parties for the successful development of both community, private, political policy and government of Kerinci Regency.Keyword : the implementation of regional autonomy and decentralization